Anisotropy Control–Induced Unique Anisotropic Thermoelectric Performance in the n‐Type Bi2Te2.7Se0.3 Thin Films. Issue 11 (11th September 2019) - Tan, Ming; Liu, Wei‐Di; Shi, Xiao‐Lei; Gao, Han; Li, Hui; Li, Cong; Liu, Xiao‐Biao; Deng, Yuan; Chen, Zhi‐Gang
Abstract: Anisotropic Bi2 Te3 ‐based thermoelectric materials have drawn extensive interest in the past decades. Here, n‐type Bi2 Te2.7 Se0.3 films with superhigh figure of merit are developed through anisotropy control via tuning an external electric field and deposition anisotropy. It is found that the angle of interplanar grain boundaries between (0 1 5) and (0 1 11) planes can be tuned by the applied external electric field, which leads to the strengthened anisotropy of electron mobility and simultaneously maintains low lattice thermal conductivity. Dominated by the unique change in the anisotropy of both lattice thermal conductivity and electron mobility, a record‐high zT value of ≈1.6 at room temperature can be achieved in the as‐deposited n‐type Bi2 Te2.7 Se0.3 film under 20 V external electric field. This work indicates that the electric field–induced deposition anisotropy control can be used to develop high‐performance Bi2 Te3 ‐based thermoelectric films. Abstract : A facile thermal evaporation–deposition technique is used to accurately control the anisotropy and corresponding grain boundaries of n‐type Bi2 Te2.7 Se0.3 film by tuning the applied external electric field. The carefully controlled angular grain boundaries introduce additional energy filtering effect and maintain low lattice thermal conductivity, which in turn lead to unique anisotropy of thermoelectric performance and record‐high figure of merit of 1.6.